Repetitive TMS of the somatosensory cortex improves writer's cramp and enhances cortical activity - Havránková, Petra; Jech, Robert; Walker, Nolan D; Operto, Grégory; Tauchmanová, Jana; Vymazal, Josef; Dušek, Petr; Hromčík, Martin; Růžička, Evžen (Neuro-endocrinology letters, 2010)
Since the somatosensory system is believed to be affected in focal dystonia, we focused on the modulation of the primary somatosensory cortex (SI) induced by repetitive transcranial magnetic stimulation (rTMS) in order to improve symptoms of writer's cramp. Patients with writer's cramp (N=9 in the pilot study and N=11 in the advanced study) were treated with 30-minute 1 Hz real- or sham-rTMS of the SI cortex every day for 5 days. Before and after rTMS, 1.5 T fMRI was examined during simple hand movements. While in the pilot study the rTMS coil was navigated over the SI cortex with a maximum of blood oxygenation-level dependent (BOLD) signal induced by passive movement, patients in the advanced study had the coil above the postcentral sulcus. After real-rTMS, 4 pilot study patients and 10 advanced study patients experienced subjective and objective improvement in writing, while only minimal changes were observed after sham-rTMS. Patients involved in the active movement task exhibited a rTMS-induced BOLD signal increase bilaterally in the SI cortex, posterior parietal cortex and in the supplementary motor area (P<0.001 corrected). After sham-rTMS, no BOLD signal changes were observed. In conclusion, 1 Hz rTMS of the SI cortex can improve writer's cramp while increasing the cortical activity in both hemispheres. Handwriting improved in most patients, as well as the subjective benefit, and lasted for 2-3 weeks. The beneficial effects of rTMS paralleled the functional reorganization in the SI cortex and connected areas, reflecting the impact of somatosensory system on active motion control.
Keywords: placebo; dospělí; Handwriting; Pilot Projects; Magnetic Resonance Imaging; Humans; lidé středního věku; Middle Aged; Models, Biological; magnetická rezonanční tomografie; psaní rukou; Cerebral Cortex; transkraniální magnetická stimulace; Transcranial Magnetic Stimulation; mužské pohlaví; mapování mozku; biologické modely; Adult; Placebos; Dystonic Disorders; somatosenzorické korové centrum; mozková kůra; dystonické poruchy; Somatosensory Cortex; ženské pohlaví; Radiation; Brain Mapping; lidé; záření; pilotní projekty; Male; Female